The Effect of Various Hot Environments on Physiological Responses and Information Processing Performance Following Firefighting Activities in a Smoke-Diving Room - Rasoul Hemmatjo; Majid Motamedzade; Mohsen Aliabadi; Omid Kalatpour; Maryam Farhadian (Elsevier, 2017)
Background: Fire service workers often implement multiple duties in the emergency conditions, with such duties being mostly conducted in various ambient temperatures. Methods: The aim of the current study was to assess the firefighters' physiological responses, information processing, and working memory prior to and following simulated firefighting activities in three different hot environments. Seventeen healthy male firefighters performed simulated firefighting tasks in three separate conditions, namely (1) low heat (LH; 29â31Â°C, 55â60% relative humidity), (2) moderate heat (MH; 32â34Â°C, 55â60% relative humidity), and (3) severe heat (SH; 35â37Â°C, 55â60% relative humidity). It took about 45â50 minutes for each firefighter to finish all defined firefighting activities and the paced auditory serial addition test (PASAT). Results: At the end of all the three experimental conditions, heart rate (HR) and tympanic temperature (TT) increased, while PASAT scores as a measure of information processing performance decreased relative to baseline. HR and TT were significantly higher at the end of the experiment in the SH (159.41Â±4.25 beats/min; 38.22Â±0.10Â°C) compared with the MH (156.59Â±3.77 beats/min; 38.20Â±0.10Â°C) and LH (154.24Â±4.67 beats/min; 38.17Â±0.10Â°C) conditions (p<0.05). There was no significant difference in PASAT scores between LH and MH (p>0.05). Nonetheless, there was a measurable difference in PASAT scores between LH and SH (p<0.05). Conclusion: These consequences demonstrate that ambient temperature is effective in raising the physiological responses following firefighting activities. It is therefore argued that further increase of ambient temperature can impact firefighters' information processing and working memory during firefighting activity. Keywords: firefighting, hot environment, information processing, physiological responses, working memory